성문법체제에서 관습법의 성립과 효력 - 손상식(Son, Sang-sik) (법학연구, 2020)
관습법은 “사회의 거듭된 관행으로 생성한 사회생활규범이 사회의 법적 확신과 인식에 의하여 법적 규범으로 승인·강행되기에 이른 것”을 말한다. 私法의 영역에서는 관습법과 상관습법으로 존재한다. 그밖에 행정법의 영역에서는 행정관습법으로, 형법의 영역에서는 관습형법으로, 그리고 헌법의 영역에서는 관습헌법 등으로 존재한다. 관습법이 성립하기 위해서는 객관적 요소로서 ‘거듭된 관행’과 주관적요소로서 ‘국민의 법적 확신’을 필요로 한다. 그밖에 관습법이 성립하기위해서는 국가의 승인이 있어야 한다거나 전체 법질서에 반하지 않을 것을 요건으로 하지는 않는다고 보아야 한다. 관습법이 그 영역에 따라 상관습법, 행정관습법, 관습형법, 그리고 관습헌법 등으로 구별되더라도, 이것이 곧 관습법의 우열 내지 효력의 차등을의미하는 것은 아니라고 할 것이다. 법규범의 효력은 규율사항이 아니라법형식에 의해 결정되므로, 규율사항을 기준으로 관습법의 효력을 결정할 수는 없다고 할 것이다. 성문법체제에서 헌법, 법률, 대통령령 등이 제정의 주체 및 절차에 따라 그 형식이 구별되는 것과는 달리, 관습법은 동일한 주체 및 절차를 거쳐 성립되고 그 형식은 관습법의 형태로 동일하기 때문에 관습법의 규율사항에 따라 차등적 효력을 갖는 것으로 볼 수는 없다. 국회는 헌법에 규정하고 있는 사항이나 금지하고 있는 사항을 제외하고는 모든 사항에 대해 법률로 규율할 수 있는 포괄적인 입법권을 부여받고 있다. 그러한 법률의 흠결을 메우기 위해 관습법이 존재할 수 있다. 그렇다면 그 관습법은 법률을 보충하고 있다는 점에서 법률과 동일한 효력을 갖는 것으로 볼 수 있을 것이다. 그리고 정당한 절차에 따라 제정된 법규범이 국민의 의사에 합치되지않는다고 하여 새로운 관습법을 만들어 구 성문법의 효력을 상실시키는것은 결국 성문법체제가 의도했던 법적 안정성과 예측가능성을 부인하는것과 다르지 않기 때문에 허용될 수 없을 것이다. Customary law refers to “social life norms derived from the repeated practice of society being approved and enforced as legal norms by the legal conviction and awareness of society.” In the domain of private law, it takes the forms of customary law and commercial customary law. In the domain of administrative law, it takes the forms of administrative customary law. It exists as customary criminal law in the domain of criminal law and as customary constitutional law in the domain of constitutional law. The requirements of customary law include “repeated practice” as an objective element and “people’s legal conviction” as a subjective one. Other requirements of customary law don’t include an approval from the state and no violation of the overall legal order. Customary law is distinguished as commercial customary law, administrative customarylaw, customary criminal law, and customary constitutional law according to the different domains, but it does not indicate the superiority and inferiority or differentiating effect of customary law. Since the effect of legal norms is determined by legal forms rather than regulatory items, there is no deciding the effect of customary law according to regulatory items. In the statute law system, the constitution, laws, and presidential decrees have different forms according to the subjects and procedures of enactment. Unlike statute law, customary law is established according to the same subjects and procedures with the same form of customary law, which means that customary law has no differentiating effect according to regulatory items. The National Assembly is granted comprehensive legislative powers to regulate all matters by law, except as stipulated or prohibited by the Constitution. Customarylaw can exist to supplement the defect of the laws. If so, the customary law will have the same effect as the law as it supplements the law. It will not be allowed to make new customary law and make the old statute law lose its effect just because the legal norms enacted according to a just procedure do not agree with the intent of people. Such an attempt will deny legal stability and predictability intended by the statute law system. KCI Citation Count: 1